Mesoporous High‐Surface‐Area Copper–Tin Mixed‐Oxide Nanorods: Remarkable for Carbon Monoxide Oxidation. Issue 14 (15th June 2016) - Peng, Honggen; Liu, Yang; Li, Yarong; Zhang, Xianhua; Tang, Xianglan; Xu, Xianglan; Fang, Xiuzhong; Liu, Wenming; Zhang, Ning; Wang, Xiang
Abstract: Mesoporous, high‐surface‐area Cu–Sn mixed‐oxide nanorods were fabricated for the first time by nanocasting with the use of mesoporous KIT‐6 silica as the hard template. The Cu–Sn nanorods are significantly more active than 1 % Pd/SnO2 for the oxidation of CO and possesses long‐term durability and potent water resistance; they thus have the potential to replace noble metal catalysts for emission‐control processes. Abstract : In rod we trust : Mesoporous, high‐surface‐area Cu–Sn nanorods are successfully fabricated for the first time by nanocasting with the use of KIT‐6 silica as the hard template; these nanomaterials are significantly more active than 1 % Pd/SnO2 for the oxidation of CO, and furthermore, they have the potential to replace noble metal catalysts for emission control.